2003
DOI: 10.2105/ajph.93.9.1576
|View full text |Cite
|
Sign up to set email alerts
|

Moving to Opportunity: an Experimental Study of Neighborhood Effects on Mental Health

Abstract: This study provides experimental evidence of neighborhood income effects on mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
430
3
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 657 publications
(460 citation statements)
references
References 24 publications
24
430
3
3
Order By: Relevance
“…A better way to measure household crowding situation would require assessments of all the houses where adolescents spend time in order to grasp the whole variability of housing conditions experienced during this developmental period and during the tome between data collections. A second limit is that other aspects of housing, for example the relationships between household members, the presence of adults with specific problems [49], the disrepair that characterises many housing units in Nunavik [6] or community characteristics [59] were not taken into account, therefore not allowing to fully grasp how housing affects psychological distress in Nunavik. Also, the measurements of household overcrowding were taken at two specific moments in time, and it is possible that they do not reflect the general situation of adolescents throughout the years.…”
Section: Discussionmentioning
confidence: 99%
“…A better way to measure household crowding situation would require assessments of all the houses where adolescents spend time in order to grasp the whole variability of housing conditions experienced during this developmental period and during the tome between data collections. A second limit is that other aspects of housing, for example the relationships between household members, the presence of adults with specific problems [49], the disrepair that characterises many housing units in Nunavik [6] or community characteristics [59] were not taken into account, therefore not allowing to fully grasp how housing affects psychological distress in Nunavik. Also, the measurements of household overcrowding were taken at two specific moments in time, and it is possible that they do not reflect the general situation of adolescents throughout the years.…”
Section: Discussionmentioning
confidence: 99%
“…185 Although a social drift explanation (ie, people with mental health problems being more likely to move into poor neighborhoods) could at least partially explain some associations between the built environment and negative emotional states or poor mental health, it also has been shown that moving to less disadvantaged neighborhoods appears to decrease psychological distress. 186 Thus, economic, social, and physical environment factors appear to contribute to chronic negative psychological states, which may result in dysregulation of the autonomic nervous system 187 and associated increased blood pressure, greater adiposity, and insulin resistance (Biological Mechanisms section); increased likelihood of unhealthy behaviors (Behavioral Mechanisms section); additional chronic life stress [188][189][190][191][192][193][194][195][196] ; and the development and progression of CVD. Research in this area is continuing, [197][198][199][200] and inclusion of racial/ethnic and socioeconomically diverse populations in this research will be critical.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…In fact, recent work has highlighted the link between community-level prejudice and health outcomes (Blair and Brondolo 2017;Orchard and Price 2017). Moreover, researchers have found a variety of contextual effects on mental health outcomes (Hill and Maimon 2013;Ivory et al 2011;Leventhal and Brooks-Gunn 2003;Schulz et al 2000) including on college and university campuses (Byrd and McKinnery 2012).…”
Section: Introductionmentioning
confidence: 99%